Municipal Solid Waste Generation in Birgunj Metropolitan City, Nepal: Quantitative and Qualitative Analysis - Patel, Niranjan; Shrestha, Kishor Kumar (Journal of Engineering and Sciences, 2022)
Abstract available with the full text.